Drop jumping from different heights: What and when it is different in the case where jump height is similar? - Panoutsakopoulos, V.; Chalitsios, C.; Kollias, I. A. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
The purpose of this study was to identify possible differences in both descriptive (0-D) and one-dimensional (1-D) kinetic and kinematic parameters in cases where jump height is similar among drop jumps (DJ) from different heights. Volleyball players (n = 10) executed DJs from 20, 40, and 60 cm. Differences in the kinetic and kinematic parameters acquired from force-plates and video-recordings were examined in DJs with same jump height across the drop heights. Results indicated that larger (p < .05) work and braking phase power were observed in DJ60 than DJ20 and DJ40. In addition, differences (p < .05) were observed in the time curves at approximately the first 20% of ground contact time, mainly between DJ20 and DJ60. The ability to adjust to the impact parameters results in the same jump outcome in DJs from different drop heights.